The impact of Taraxacum officinale aqueous extracts on WISH cancer cell line - Husieva, O.; Baranovsky, M. (Problems of Environmental Biotechnology, 2019)
Objective: to investigate the impact of aqueous extracts of Taraxacum officinale on the WISH (monolayer) cancer cell line. Chemical composition and pharmacological properties of dandelion are considered. Methods: this article considers microscopic method based on inhibition and percentage determination of cancer cell lines. Results: experiment shows that dandelion dried and fresh extracts (from root and leaves) can be used against cervix cancer cells – human WISH (monolayer) cell line.